Personalized neoadjuvant strategy using 70-gene assay to increase breast-conserving surgery in ER+/HER2– breast cancer - Wonshik Han; Eunhye Kang; Ji Gwang Jung; Hong-Kyu Kim; Han-Byoel Lee; Jisun Kim; Sae Byul Lee; Hee-Chul Shin; Chan Sub Park; Min-Ki Seong; Hyun-Ah Kim; Eun-Kyu Kim; et al. (npj Breast Cancer)
Abstract We investigated whether tailored neoadjuvant therapy (chemotherapy [NCT] or endocrine therapy [NET]) guided by a 70-gene assay could improve breast-conserving surgery (BCS) rates among patients with ER-positive/HER2-negative breast cancer initially deemed ineligible for BCS. Of 130 prospectively enrolled patients (stage II–IIIA, across four Korean centers), 92 were analyzed. Patients classified as high genomic risk received NCT, while low-risk patients underwent NET (letrozole ± leuprolide for premenopausal women) for 16–24 weeks. The primary endpoint—achieving the surgeon-defined target tumor size for BCS—was reached in 69.6% (95% CI: 59.1–78.7%), significantly surpassing the predefined goal of 50.8% (p < 0.05). The actual overall BCS rate was 59.8% (64.7% NCT, 45.8% NET). Pathologic complete response occurred in 2.2%, exclusively in the NCT group. Thus, pretreatment genomic profiling effectively guided therapy selection, substantially increasing BCS eligibility while sparing low-risk patients unnecessary chemotherapy toxicity.